Entamoeba histolytica Cysteine Proteinase 5 Evokes Mucin Exocytosis from Colonic Goblet Cells via αvβ3 Integrin - Cornick, Steve (PLoS Pathog, 2016)
Critical to the pathogenesis of intestinal amebiasis, Entamoeba histolytica (Eh) induces mucus hypersecretion and degrades the colonic mucus layer at the site of invasion. The parasite component(s) responsible for hypersecretion are poorly defined, as are regulators of mucin secretion within the host. In this study, we have identified the key virulence factor in live Eh that elicits the fast release of mucin by goblets cells as cysteine protease 5 (EhCP5) whereas, modest mucus secretion occurred with secreted soluble EhCP5 and recombinant CP5. Coupling of EhCP5-αvβ3 integrin on goblet cells facilitated outside-in signaling by activating SRC family kinases (SFK) and focal adhesion kinase that resulted in the activation/phosphorlyation of PI3K at the site of Eh contact and production of PIP3. PKCδ was activated at the EhCP5-αvβ3 integrin contact site that specifically regulated mucin secretion though the trafficking vesicle marker myristoylated alanine-rich C-kinase substrate (MARCKS). This study has identified that EhCP5 coupling with goblet cell αvβ3 receptors can initiate a signal cascade involving PI3K, PKCδ and MARCKS to drive mucin secretion from goblet cells critical in disease pathogenesis.